PENGARUH PERSEPSI KUALITAS PRODUK, PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN SEPEDA MOTOR MATIC HONDA DI KOTA PEKANBARU - Rinando, Putra Aulia; Zulkarnain, Zulkarnain; Henni, Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of perceived product quality, promotion and price on purchasing decisions and consumer satisfaction of Honda matic in Pekanbaru City. Sample in this study was 160 people with conditions, aged over 17 years and purchased a Honda matic in Pekanbaru City in 2015-2019. Sampling using nonprobability sampling method with purposive sampling. To test the hypothesis in this study, researchers used SEM-PLS analysis with the help of the WarpPLS 6.0 software program. The results showed that: 1) Perceptions quality product and price have a positive and significant effect on purchasing decisions for Honda matic in Pekanbaru City, 2) Promotion has a positive and not significant effect on purchasing decisions for Honda matic in Pekanbaru City, 3) Purchasing decisions have a positive and significant effect on customer satisfaction for Honda matic in Pekanbaru City, 4) Perceptions quality product and price have a positive and significant effect on consumer satisfaction through purchasing decisions for Honda matic in Pekanbaru City, 5) Promotion has a positive effect and not significant to consumer satisfaction through the decision to purchase Honda matic in Pekanbaru City.Keywords: Perception Quality Product, Promotion, Price, Purchase Decision and Consumer Satisfaction